'I'm lost' – a qualitative analysis of student teams' strategies during their first experience in problem-based learning. (3rd May 2020) - Mabley, Seren; Ventura-Medina, Esther; Anderson, Anthony
ABSTRACT: Future global challenges that engineering graduates face have placed demands on engineering education and how graduates develop competency in collaborative problem-solving. Such demand has seen an increase in the use of pedagogies like problem-based learning (PBL) that provide opportunities for developing collaborative problem-solving skills. PBL has been well studied however there is still much to understand about 'how' students solve problems collaboratively in PBL settings. This work investigates the processes taking place when students set out to solve problems in a group. Naturalistic data from video recordings of participants in chemical process design PBL sessions is used. Participants conversations were transcribed and their language analysed using qualitative content analysis to provide a description of 'what' strategies students use. The findings indicate that students tend to adhere to relatively rigid structures and minimise effort when tackling unfamiliar ill-defined problems. Additionally, students appear to struggle making connections between knowledge domains.